Comparative Analysis of Variable Costing and Full Costing Methods for Profit Planning and Managerial Decision-Making - Saltzman Bhimani; Anderson Christianto (Institute of Accounting Research and Novation (IARN), 2023)
This research investigates the comparative effectiveness of variable costing and full costing methods in profit planning and managerial decision-making within organizational contexts. Through a comprehensive review of existing literature, empirical data analysis, and theoretical frameworks, the study aims to provide insights into the implications of each costing method for organizational performance and strategic decision-making. The research begins with an exploration of the historical development and adoption of variable costing and full costing methods in accounting and managerial decision-making. Drawing on economic theory, regulatory frameworks, and organizational practices, the study examines the theoretical underpinnings and practical applications of these costing methods. Using a mixed-methods approach, the research employs both quantitative analysis of financial performance metrics and qualitative analysis of managerial perspectives and decision-making processes. Findings indicate distinct patterns and significant differences between variable costing and full costing methods, particularly in terms of cost behavior, cost-volume-profit relationships, and strategic implications for resource allocation and pricing strategies. Interpreting the results within the context of existing theory and literature, the study identifies implications for businesses and managerial decision-making. It underscores the importance of cost visibility, decision-making flexibility, and regulatory compliance in choosing the appropriate costing method to enhance organizational performance and strategic positioning.